The necessity of union - Criner, Lilian Clyde (My University, 1892)
Introduction: When the Articles of Confederation were cast aside and the new constitution was adopted, it was said that we had a “perpetual union made more perfect”. Today we have need of a similar clause, not constitutional or statutory, to be handed down in posterity as a monument of an ancient liberty, but, written upon the hearts of men. Though the last gun of the Rebellion was heard nearly thirty years ago, there is not yet a perfect union. There are men in the North and in the South, who fought through the Civil War, and still wish to continue the fight and if it were possible, when they die, leave the remainder of their unsatisfied ambition to their descendants. The war has come and gone; it was inevitable. Compromises were adopted, but they only added fuel to the conflict that was to follow. There was no halfway ground, there must either be a complete union of the states or none at all.
Citation: Criner, Lilian Clyde. The necessity of union. Senior thesis, Kansas State Agricultural College, 1892.
Morse Department of Special Collections
Keywords: Civil war; History; Theses; Manuscripts (documents)